Simple Two-Dimensional Echocardiographic Scoring System for the Estimation of Left Ventricular Filling Pressure - Murayama, Michito; Iwano, Hiroyuki; Nishino, Hisao; Tsujinaga, Shingo; Nakabachi, Masahiro; Yokoyama, Shinobu; Aiba, Miho; Okada, Kazunori; Kaga, Sanae; Sarashina, Miwa; Chiba, Yasuyuki; Ishizaka, Suguru; et al. (Journal of the American Society of Echocardiography, 2021)
When left ventricular filling pressure (LVFP) increases, the mitral valve opens early and precedes tricuspid valve opening in early diastole. The authors hypothesized that a visually assessed time sequence of atrioventricular valve opening could become a new marker of elevated LVFP. The aim of this study was to test the diagnostic ability of a novel echocardiographic scoring system, the visually assessed time difference between mitral valve and tricuspid valve opening (VMT) score, in patients with heart failure. One hundred nineteen consecutive patients who underwent cardiac catheterization within 24 hours of echocardiographic examination were retrospectively analyzed as a derivation cohort. In addition, a prospective study was conducted to validate the diagnostic ability of the VMT score in 50 patients. Elevated LVFP was defined as mean pulmonary artery wedge pressure (PAWP) ≥ 15 mm Hg. The time sequence of atrioventricular valve opening was visually assessed and scored (0 = tricuspid valve first, 1 = simultaneous, 2 = mitral valve first). When the inferior vena cava was dilated, 1 point was added, and VMT score was ultimately graded as 0 to 3. Cardiac events were recorded for 1 year after echocardiography. In the derivation cohort, PAWP was elevated with higher VMT scores (score 0, 10 ± 5; score 1, 12 ± 4; score 2, 22 ± 8; score 3, 28 ± 4 mm Hg; P < .001, analysis of variance). VMT score ≥ 2 predicted elevated PAWP with accuracy of 86% and showed incremental predictive value over clinical variables and guideline-recommended diastolic function grading. These observations were confirmed in the prospective validation cohort. Importantly, VMT score ≥ 2 discriminated elevated PAWP with accuracy of 82% in 33 patients with monophasic left ventricular inflow in the derivation cohort. Kaplan-Meier analysis demonstrated that patients with VMT scores ≥ 2 were at higher risk for cardiac events than those with VMT scores ≤ 1 (P < .001). VMT scoring could be a novel additive marker of elevated LVFP and might also be associated with adverse outcomes in patients with heart failure. •MV opening becomes early in accordance with elevated LVFP.•A VMT score using the time sequence of atrioventricular valve opening is proposed.•VMT score was associated with elevation of LVFP in patients with HF.•VMT score was also associated with future adverse events in HF.